Análise dos agentes etiológicos, síndromes infecciosas e fatores de risco em neonatos críticos: histórico de quatro anos - Levenhagen, Maria Margarida Morena Domingos (2016)
In recent decades, the major advance in the intensive care promoted profound changes in the evolution and prognosis of patients. However, while extending the life expectancy of these patients, some procedures may increase the risk of clinical complications, such as Health Care Associated Infections (HAIs). The HAIs are the main cause of mortality and morbidity in Neonatal Intensive Care Units (NICU). As the clinical characteristics of the newborn and the profile of the microorganisms related to HAIs vary greatly according to the sample population, monitoring these factors can contribute the adequacy of the Neonatal Intensive Care Units to their real demands. Therefore, our study aimed to analyze the clinical profile of newborns, as well as the characteristics of the main infectious agents related to conditions of HAIs in the Neonatal Intensive Care Unit, at the Clinical Hospital of the Federal University of Uberlandia, in the period of 2011-2014. It was performed a retrospective cohort study, by analyzing the epidemiological surveillance of National Healthcare Safety Network (NHSN) and laboratory data obtained from medical records of patients. From 1126 neonates, 499 (44.3%) were female and 618 (54.8%) were male; 58.6% of newborns had a low extreme weight (≤1000g) and approximately 70% were identified as preterm (IG≤37semanas). The main clinical admission reason to the NICU was due to respiratory issues (75%). Among the main diagnoses, 38.5% of neonates with TTN/SAP and 23.9% with SMH. We observed 238 cases of HAIs, and the most frequent species were Staphylococcus epidermidis (32,5%) and S. aureus (14.8%). The bacteremia bloodstream was predominant in 63.5% of cases. It was also isolated 33 fungal agents, 66,6% in blood cultures. Risk factors related to HAIs according to χ2 test or Fisher exact test (P≤0.05) were: sex, low birth weight, gestational age, time of hospitalization, use of parenteral nutrition, mechanical ventilation, use of phlebotomy, PIC and umbilical catheter use. The low weight and prematurity were the factors that had a strong impact in the clinical conditions that led to admission on NICU. The bloodstream infection stood out as the main infectious syndrome, and the Staphylococcos epidemidis the most common etiologic agent. Several risk factors were statistically significant for the occurrence of HAIs in the unit, especially central venous catheters. This further reinforces the importance of surveillance added to more rigor of infection control practices.